2012
DOI: 10.1364/ao.51.007080
|View full text |Cite
|
Sign up to set email alerts
|

Computation of diffracted fields for the case of high numerical aperture using the angular spectrum method

Abstract: The angular spectrum (AS) method is a popular solution to the Helmholtz Equation without the use of approximations. In this work, new criteria on sampling requirements are derived using the Wigner distribution (WD). It is shown that for the case of high numerical aperture the conventional AS method requires a very large amount of zero-padding, making it impractical due to requirements on memory and computational effort. This work proposes the use of a modified AS algorithm that evaluates only non-zero componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(32 citation statements)
references
References 21 publications
1
26
0
2
Order By: Relevance
“…18, will increase the acceptable bandwidth of the input wave field, but at the cost of an increased number of samples. This has also been discussed in [2,5,6,17]. Especially, for the case of X-ray optics, where wavelengths are very small compared to the sampling window size, a sufficient sampling rate can be harder to obtain than a sufficient sampling window size.…”
Section: Discussion On the Sampling Limitmentioning
confidence: 97%
See 3 more Smart Citations
“…18, will increase the acceptable bandwidth of the input wave field, but at the cost of an increased number of samples. This has also been discussed in [2,5,6,17]. Especially, for the case of X-ray optics, where wavelengths are very small compared to the sampling window size, a sufficient sampling rate can be harder to obtain than a sufficient sampling window size.…”
Section: Discussion On the Sampling Limitmentioning
confidence: 97%
“…For a given bandwidth of the input wave field a given size of the sampling window and a given offset between the sampling windows, the propagation can only be done up to a certain distance limit without loss of accuracy. Detailed discussions on this limit for the angular spectrum and shifted angular spectrum method, which is also true for this modified method, can be found for example in [4][5][6]17]. To enable propagation for distances above the distance limit one has to choose another method for example [4][5][6].…”
Section: Discussion On the Sampling Limitmentioning
confidence: 99%
See 2 more Smart Citations
“…The accuracy of ORC-FBPP can be significantly improved [21] by replacing the approximated Rytov propagation with the rigorous angular spectrum (AS) propagation method [28], which enables obtaining ORC-EDOF-FBPP. While in [21] the solution is provided for ORC-HT, in this paper it will be shown that the same principle holds also for ISC-HT.…”
Section: Rigorous Angular Spectrum Backpropagation For Off-axis Fieldsmentioning
confidence: 99%